Elvis & Nixon [videorecording (DVD)] - Shannon, Michael, 1974-; Spacey, Kevin; Pettyfer, Alex, 1990-; Knoxville, Johnny, 1971- (Sony Pictures Home Entertainment Inc., 2016)
The story of the infamous meeting between Elvis Presley and Richard Nixon in 1970, which was immortalized in the most requested photograph in the National Archives.